The rheological properties of nano yttria stabilised zirconia (YSZ) for micro metal injection molding - Hafizawati, Zakaria; Norhamidi, Muhamad; Abu Bakar, Sulong; Farhana, Foudzi; Mohd. Halim Irwan, Ibrahim (SIRIM, 2011)
4th Malaysian Powder Metallurgy Symposium (MPMS) and Malaysian Metallurgical Conference (MMC) 2010 organized by SIRIM Berhad on 22nd - 23rd November 2010 at Parkroyal Hotel, Penang, Malaysia.